A Note on the Specific Gravity of Eucalyptus Species from Different Localities - Shukla, N. K.; Rajput, S. S. (Indian Forester, 1981)
Eucalypts have been planted extensively in different parts of this country. For quicker evaluation of plantations for their industrial utilisation its specific gravity is often required. In the present paper specific gravity of different species of the Eucalyptus tested from 40 different localities has been reported and discussed.